Mucoprotectants - Sung Eun Kim (Yong Chan Lee, 2022)
The gastric mucosa is constantly exposed to gastric acid and pepsin. Moreover, various factors, such as nonsteroidal anti-inflammatory drugs, Helicobacter pylori infection, ethanol, stress, and aging, can damage the gastrointestinal mucosa. Nevertheless, even under these harsh conditions, the gastric mucosa is structurally maintained by various processes, referred to as "defense mechanisms." Mucosal defense mechanisms are complicated; however, the most important elements are known to be the gastric epithelium and mucus layer, which are stimulated by prostaglandins and nitric oxide. Peptic ulcers result from an imbalance between these aggressive and defensive factors. Methods to prevent or treat peptic ulcers can be classified into two classes: 1) inhibition of gastric acid secretion and 2) promotion of mucosal defense factors. Drugs that reduce gastric acid secretion include proton pump inhibitors, histamine H2 antagonists, and potassium-competitive acid blockers. Mucoprotectants prevent peptic ulcers by promoting peptic ulcer healing. Mucoprotectants can work by two main mechanisms of action; one is independent of prostaglandins, and the other is related to prostaglandin activity. Bismuth, sucralfate, and misoprostol have been traditionally used to protect the gastric mucosa from gastric acid and pepsin. Currently, several mucoprotectants, such as rebamipide, ecabet sodium, polaprezinc, teprenone, and DA-9601, are prescribed in clinical practice. This review aims to provide information to clinicians by examining the characteristics of each drug, including their mechanism of action, research results, effective dose, and side effects.